Efek Kompetensi Terhadap Prestasi Kerja Karyawan - Achmad Syahlani; Desy Setyorini (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
One of the factor that can affect employee performance is the competence of the employee. The purpose of this study is to test the significance of the relationship and to form and test the linearity and significance of the linear regression equation between competence and employee performance. The study was conduct at Cipto Mangunkusumo Kencana Hospital, Jakarta, the population of this study was all of its employees. From this population, a sample of 49 employees was taken using a simple random sampling technique. This study used a causal survey method. The research data were collected through a research instrument in the form of a questionnaire with a 5-level Likert scale, then processed and analyzed using regression analysis techniques and linear correlation using the SPSS program. The results of this study indicate that there is a positive relationship between competence and employee performance, which can be formed in a significant linear regression equation to state the relationship